Culture, Urbanism and Planning. - Monclús, F. J. (Francisco Javier) (Heritage, culture, and identity., 2007)
This volume brings together a team of leading specialists to examine the policies of image and city marketing which have developed over the past 15 years and whether these are a continuity of earlier strategies.